Pengelolaan Kendaraan Dinas Dalam Mewujudkan Tertib Administrasi Pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Bogor - Fadila Khaerunnisa; Cecep Wahyu Hoerudin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
The purpose of this research is to describe how the management of official vehicles at Financial and Asset Management Agency of Bogor Regency is based on Permendagri Number 19 of 2016. The research method used is descriptive method with a qualitative approach. Data collection techniques through observation, interviews and documentation. The results showed that the management of official vehicles BPKAD of Bogor Regency had been carried out in accordance with Permendagri Number 19 of 2016. This was done for the sake of creating an orderly administration in the management of regional assets. Asset inventory is carried out every five years by inputting official vehicle data in The Application of Information Technology of Local Goods Cycle (ATISISBADA) so that they no longer use the Goods Inventory Card (KIB). However, there are still obstacles, namely the problem of incomplete and inaccurate asset inventory data. The legal audit has been carried out properly, as can be seen from the clear status of control of official vehicles. The assessment is carried out by KJPP. Optimization of official vehicles has been carried out well. Supervision is carried out periodically then control is carried out by following up if there are errors in the management of official vehicles. The activities of managing official vehicles are made easier by the existence of ATISISBADA.